3f-8=10f+9-8f

Simple and best practice solution for 3f-8=10f+9-8f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3f-8=10f+9-8f equation:


Simplifying
3f + -8 = 10f + 9 + -8f

Reorder the terms:
-8 + 3f = 10f + 9 + -8f

Reorder the terms:
-8 + 3f = 9 + 10f + -8f

Combine like terms: 10f + -8f = 2f
-8 + 3f = 9 + 2f

Solving
-8 + 3f = 9 + 2f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-2f' to each side of the equation.
-8 + 3f + -2f = 9 + 2f + -2f

Combine like terms: 3f + -2f = 1f
-8 + 1f = 9 + 2f + -2f

Combine like terms: 2f + -2f = 0
-8 + 1f = 9 + 0
-8 + 1f = 9

Add '8' to each side of the equation.
-8 + 8 + 1f = 9 + 8

Combine like terms: -8 + 8 = 0
0 + 1f = 9 + 8
1f = 9 + 8

Combine like terms: 9 + 8 = 17
1f = 17

Divide each side by '1'.
f = 17

Simplifying
f = 17

See similar equations:

| y^4-3y^2-2y=0 | | n^2-34n+64=0 | | 2x^5+6x^4-4x^2=0 | | 1/4x-3/5=1 | | 8.1=5n-6.4 | | 6py/-5y | | -11w+w=-10 | | -2(p-10)+11=5 | | (x^2+8x)+16=25 | | 2(3x+4)=-16 | | -3d+-d=-20 | | 21k^3-18k^2+7k-6=0 | | 6x^3+15x^2-16x-40=0 | | -10+11u=2+8u | | 2y+-7=19 | | -(-5n+7)-1=2(n+5) | | -6m+18=-8m-20 | | -2=m-16/-1 | | (-0.2)(-0.58)= | | (x+5)(6x-7)=0 | | 7(7x+6)-x=8(4+6x) | | 3k=2k-16 | | f(x)=(2x-1)(x+2)(x+3) | | (7x-1)(x-7)=0 | | -4(w-7)=-7w+19 | | 18=3(j-13) | | 2(4+7x)=-3(1-4x)+5 | | 2u+38=7(u-1) | | r-10/3=3 | | .42/7.00=x/100 | | (2x-1)(2x+7)=0 | | 3(p-13)+4=13 |

Equations solver categories